A Development of Supporting System for Historical Heritage Based Tourism - Boonmee, Salinun; Somsuphaprungyos, Suwit; Natho, Parinya; Boonying, Sangtong (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2024)
Tourism is a major economic contributor in Thailand. With the richness of historical heritage recognized as world heritages, Phra Nakhon Si Ayutthaya province is a famous destination for tourists who enjoy historical and cultural tourism. This work presents a development of a supporting system for tourism in Phra Nakhon Si Ayutthaya province in regarding of historical and cultural aspects of heritages. This work designs an ontology to represent a relation network of properties from tourist attractions based on historical and cultural relationship among them. Instances which are the heritages hence are related and can be visualized in a form of a graph. The suggestion module is designed to provide related tourist destination following the relations from the generated knowledge graph based on the initial query of a user. The experiment results signify that the system revealed hidden historical relations of destinations to users and made them learn the values of history lied within heritages. Furthermore, 87.5% of participants decided to make a tour plan following the suggested destinations since they found the linking in historical values to be more meaningful and interesting.